1995
DOI: 10.1007/bf02353468
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancies in pharmacokinetic parameter estimation between bolus and infusion studies in the perfused rat hindlimb

Abstract: Isolated, perfused rat hindlimb consists of skeletal muscle, skin, bone, and adipose. Hence, it is a heterogeneous preparation composed of slowly equilibrating tissues of different characteristics and fractional flow rates. This paper shows how caution should be exercised in interpreting the results following bolus administration and subsequent statistical moment analysis of intravascular markers (51Cr-erythrocytes and 125I-albumin) and lipophilic barbiturates. For the intravascular markers, the events in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…However, consistent with events shown in Fig. 8a, Anne Heatherington and Malcolm showed that intravascular distribution in the hindlimb after bolus administration can be overshadowed by events in the connecting tubing and cannulas, resulting in discrepancies between bolus and infusion pharmacokinetics [138]. Malcolm’s group has also applied the dispersion model to describe the disposition of markers and a series of barbiturates in the perfused hind leg [139].…”
Section: Pharmacokinetics In Other Perfused Organsmentioning
confidence: 85%
“…However, consistent with events shown in Fig. 8a, Anne Heatherington and Malcolm showed that intravascular distribution in the hindlimb after bolus administration can be overshadowed by events in the connecting tubing and cannulas, resulting in discrepancies between bolus and infusion pharmacokinetics [138]. Malcolm’s group has also applied the dispersion model to describe the disposition of markers and a series of barbiturates in the perfused hind leg [139].…”
Section: Pharmacokinetics In Other Perfused Organsmentioning
confidence: 85%
“…This type of anomaly has been reported previously in the perfused rat hind limb. Heatherington and Rowland [24] noted a consistent overestimation of the vascular space in the perfused hind limb by using bolus methods compared with values obtained by using whole body experiments. They suggested that transient pressure changes caused by injecting the bolus could cause additional vessels to be recruited.…”
Section: Discussionmentioning
confidence: 99%